Erosive Pustular Dermatosis of the Scalp with Urate-Like Crystals - Patrick O. Emanuel; Sharad P. Paul (Case Reports in Dermatological Medicine)
Follicular urate-like crystals were first described in Necrotizing Infundibular Crystalline Folliculitis (NICF), a rare cutaneous disorder with multiple waxy folliculocentric papules. Similar crystal accumulation may be seen within follicular infundibulae as an incidental finding. We describe a case showing identical crystals occurring within the horn-like crusts of a patient with erosive pustular dermatosis of the scalp (EPDS), a condition which due to its presentation can often be mistaken for nonmelanoma skin cancer. A brief overview of erosive pustular dermatosis of the scalp (EPDS) is presented in this paper.